Christus verus Luciferus, Demon est Deus Inversus Pekka Siitoin’s Spiritism Board - Pasanen Tero (Finland, 2022)
This article focuses on a Spiritism board, Yhteyslauta, designed in the mid-1970s by occultist neo-Nazi Pekka Siitoin. The board represents an unexplored occult subchapter of Finnish gaming culture and exhibits the Finnish esoteric tradition. In addition to analysing Yhteyslauta’s game-like elements, the article explores the board’s themes and imagery, and situates these components in the context of Siitoin’s vernacular esoteric doctrine and cosmogony.